WATER versus WATER II 5‐year update: Comparing Aquablation therapy for benign prostatic hyperplasia in 30–80‐cm3 and 80–150‐cm3 prostates - Mohamad Baker Berjaoui; David‐Dan Nguyen; Saud Almousa; Karim Daher; Neil Barber; Mo Bidair; Peter Gilling; Paul Anderson; Kevin C. Zorn; Gopal Badlani; Mitch Humphreys; Steven Kaplan; et al. (BJUI Compass)
Abstract Objective This study aims to compare the long‐term outcomes of Aquablation for small‐to‐moderate (30–80 cm3) prostates with the outcomes for large (80–150 cm3) prostates at 5‐year follow up. Methods The Waterjet Ablation Therapy for Endoscopic Resection of Prostate Tissue (WATER; NCT02505919) is a prospective, double‐blind, international clinical trial encompassing 116 patients, examining Aquablation versus transurethral resection of the prostate (TURP) for LUTS/BPH in prostates sized between 30 and 80 cm3. In parallel, WATER II (W‐II; NCT03123250), a prospective, multicentre, single‐arm international clinical trial, explores Aquablation outcomes in prostates ranging from 80 to 150 cm3. Baseline parameters and 60‐month outcomes were scrutinized using statistical analyses, including Students' t test, Wilcoxon tests for continuous variables, and Fisher's test for binary variables. Results There is a significant improvement in International Prostate Symptom Score (IPSS) from baseline to 60 months in both WATER (22.9 to 7.0) and WATER II (23.2 to 6.8) (P = 0.852). Urinary flow rate (Qmax) increased in both groups from baseline to 60 months (WATER: 9.4 to 17.3 cc/s; WATER II: 8.7 to 17.1 cc/s) (P = 0.933). Immediate and sustained enhancements were observed in IPSS and Qmax. At 5 years, a notable percentage of patients in both groups were BPH medication‐free (WATER: 99%; WATER II: 94%) (P = 0.0517) and free from surgical retreatment (WATER: 95%; WATER II: 97%) (P = 0.508). Conclusions The 5‐year follow‐up affirms that Aquablation therapy exhibits sustained outcomes, minimal irreversible complications, and low retreatment rates for treating LUTS/BPH, irrespective of prostate volume ranging from 30 to 150 cm3.